Because we cannot walk on water - Rizkallah, Meriam (AUC Knowledge Fountain, 2017)
Climate induced migration became a recognized phenomenon. Due to the adverse effects of climate change, populations in certain affected areas will start to move either as a form of adaptation or because of failure to adapt thereof. The main questions raised are concerned with the rights of the people displaced. On the other hand, what obligations do states and the international community have to provide protection for these populations. This paper argues that climate migrants are not protected from both the causes and effects of climate change. The international environment governance system does not seem to have regulated the process that guarantees global environmental protection. On the other hand, if people start to move due to the effects of climate change, they will fall from the existing gaps in the international protection system. This paper also specifically looks at the moral dimension of the phenomenon of climate change, and presents why moral questioning is of value when dealing with such contentious issue. It also speaks to the no-harm principle being a fundamental principle in international law and specifically to environmental law. Despite its importance, this principle is usually neglected when formulating policies on climate change. It argues that the no-harm principle was missing from the context of Paris Agreement, and thus kept the prospects of harm in place. It does this by its commitment to industrial growth and avoiding having emission reduction targets. As well, this paper discusses how climate migrants are not adequately addressed in Paris Agreement due to certain geopolitical settings, sustaining the possibility of them remaining highly vulnerable. This paper highlights legal and moral failure of the international society towards climate change at large and towards climate migrants in particular.